Romanian public administration reform 2.0: using innovative foresight methodologies to engage stakeholders and the public. Issue 3 (12th June 2017) - Zulean, Marian; Andreescu, Liviu; Gheorghiu, Radu; Roescu, Andra Maria; Curaj, Adrian
Abstract : Purpose: The purpose of this practice-oriented paper is to look at a recent, late-phase development in public administration (PA) reform in Romania, specifically the drafting of the recently adopted national Strategy on Strengthening the Efficiency of Public Administration (2014-2020). In particular, the paper focuses on the opportunities and limits of outsourcing the building of the vision underlying the strategy and the prioritization of strategic objectives. The article's story is also placed in the broader context of agencification literature and, more specifically, the involvement of executive agencies in policymaking. Design/methodology/approach: The paper describes the vision-building exercise, developed according to a script already tested in several sectoral strategy-making processes, and the objectives and procedure of the online participatory consultation by using an adapted real-time Delphi format (similarly tested in the recent past). Findings: The paper reports on the ways in which the output of the visioning process and of online consultations may be used to enhance a strategic process already underway. Originality/value: PA reform in post-communist countries has been among the most hotly debated, intensely pursued, yet seemingly elusive policy objectives of the transition and post-transition periods. Among pre-accession and then European Union (EU) member states, the need to get in and then to get involved in European policymaking provided some impetus for such reforms and also set substantial constraints, without however always adding much predictability or significantly streamlining the public sector. The paper contributes to this debate by proving an innovative method of devising a reform strategy by outsourcing the strategy-building process to an agency with the necessary know-how and experience.